Differential Sensitivity to Ethanol‐Induced Circadian Rhythm Disruption in Adolescent and Adult Mice. (20th December 2016) - Ruby, Christina L.; Palmer, Kaitlyn N.; Zhang, Jiawen; Risinger, Megan O.; Butkowski, Melissa A.; Swartzwelder, H. Scott
Abstract : Background: Growing evidence supports a central role for the circadian system in alcohol use disorders, but few studies have examined this relationship during adolescence. In mammals, circadian rhythms are regulated by the suprachiasmatic nucleus, a biological clock whose timing is synchronized (reset) to the environment primarily by light (photic) input. Alcohol (ethanol [EtOH]) disrupts circadian timing in part by attenuating photic phase‐resetting responses in adult rodents. However, circadian rhythms change throughout life and it is not yet known whether EtOH has similar effects on circadian regulation during adolescence. Methods: General circadian locomotor activity was monitored in male C57BL6/J mice beginning in adolescence (P27) or adulthood (P61) in a 12‐hour light, 12‐hour dark photocycle for ~2 weeks to establish baseline circadian activity measures. On the day of the experiment, mice received an acute injection of EtOH (1.5 g/kg, i.p.) or equal volume saline 15 minutes prior to a 30‐minute light pulse at Zeitgeber Time 14 (2 hours into the dark phase) and then were released into constant darkness (DD) for ~2 weeks to assess phase‐resetting responses. Control mice of each age‐group received injections but no light pulse prior to DD. Results: While adults showed the expected decrease in photic phase‐delays induced by acute EtOH, this effect was absent in adolescent mice. Adolescents also showed baseline differences in circadian rhythmicity compared to adults, including advanced photocycle entrainment, larger photic phase‐delays, a shorter free‐running (endogenous) circadian period, and greater circadian rhythm amplitude. Conclusions: Collectively, our results indicate that adolescent mice are less sensitive to the effect of EtOH on circadian photic phase‐resetting and that their daily activity rhythms are markedly different than those of adults. Abstract : Ethanol disrupts circadian rhythms in adults, but its effects during adolescence are unknown. Ruby et al. show that, in contrast to adults, adolescent mice are insensitive to the inhibitory effects of acute ethanol on light‐induced delays of the circadian locomotor activity rhythms. They also report that circadian timing in adolescents differs from that of adults in ways that may be relevant to alcohol drinking, including greater activity levels, larger light‐induced delays, and shorter endogenous circadian period.